PENGARUH POTONGAN HARGA DAN PENATAAN PRODUK DI DALAM TOKO TERHADAP PEMBELIAN IMPULSIF PADA MR. DIY KABUPATEN SIDENRENG RAPPANG - Nurwafiyyah, Auliyah; Heady S., Muhammad G. Try; Haeril, Haeril (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The current retail business competition in Indonesia is very tight, as evidenced by the number of retailers that are widely spread throughout Indonesia both local, national and international. Indonesia is one of the countries that has a high level of consumption of retail goods. The pattern of consumer behavior that can be found when in a retail store is to make spontaneous and unplanned purchases referred to as impulse purchases. The purpose of the study was to determine how much influence discounts and product arrangements in the store have on impulse purchases at MR.DIY Sidenreng Rappang Regency. This research is a quantitative study using primary data from 100 respondents at MR.DIY consumers in Sidenreng Rappang Regency. The data analysis used in this research is multiple linear regression analysis. The results of this study indicate that the discount variable has no significant effect on impulse purchases, while product arrangement in the store has a significant effect on impulse purchases.